Development of a Canva-Assisted Microblogging Model to Enhance Understanding of Fundamental Early Childhood Education Concepts - Ansori Ansori; Silmy Nurul Firdaus; Arifah Riyanto (PT MEDIA JURNAL DAN PENDIDIKAN, 2026)
This study aimed to develop a Canva-assisted microblogging model to enhance nonformal Early Childhood Education (ECE) teachers' understanding of fundamental ECE concepts. The study employed a Research and Development approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The products developed included the MIKRO Model and three Canva-assisted microblogs addressing common misconceptions in ECE practices. The MIKRO Model integrated five stages, namely Access, Identification, Review, Reflection, and Optimization, to facilitate concise, contextual, and reflective learning experiences. The model and microblogs were validated by a model expert and a media expert to determine their feasibility before implementation. A limited field trial involving 20 nonformal ECE teachers was conducted using a pretest-posttest design. The findings indicated that the MIKRO Model was feasible for implementation, with expert validation results categorizing both the model and the microblogs as feasible. Furthermore, teachers' understanding of fundamental ECE concepts improved following the intervention, as reflected in the increase in posttest scores and a moderate N-Gain score. The study concluded that the Canva-assisted MIKRO Model represented an innovative and practical alternative for supporting the professional learning of nonformal ECE teachers through concise, flexible, and reflective learning experiences.